The changing landscape of cerebral revascularization surgery: A United Kingdom experience - Gallagher, Mathew J.; Frantzias, Joseph; Kailaya-Vasan, Ahilan; Booth, Thomas C.; Tolias, Christos M. (Frontiers in Radiology, 2022)
Objective We describe the chronological trends in cerebral revascularization surgery through a single-surgeon experience; and we review whether in the context of giant and fusiform cerebral aneurysms, flow-diverting stents have impacted on the use of cerebral revascularization surgery. Methods We review our single institution prospectively collected database of cerebral revascularization procedures between 2006 and 2018. Comparing this to our database of flow-diverting endovascular stent procedures, we compare the treatment of fusiform and giant aneurysms. We describe patient demographics, procedural incidence, complications, and outcomes. Results Between 2006 and 2018, 50 cerebral revascularization procedures were performed. The incidence of cerebral revascularization surgery is declining. In the context of giant/fusiform aneurysm treatment, the decline in cerebral revascularization is accompanied by a rise in the use of flow-diverting endovascular stents. Thirty cerebral revascularizations were performed for moyamoya disease and 11 for giant/fusiform aneurysm. Four (14%) direct bypass grafts occluded without neurological sequela. Other morbidity included hydrocephalus (2%), transient ischemic attacks (2%), and ischemic stroke (2%). There was one procedure-related mortality (2%). Flow-diverting stents were inserted for seven fusiform and seven giant aneurysms. Comparing the treatment of giant/fusiform aneurysms, there was no significant difference in morbidity and mortality between cerebral revascularization and flow-diverting endovascular stents. Conclusion We conclude that with the decline in the incidence of cerebral revascularization surgery, there is a need for centralization of services to allow high standards and outcomes to be maintained.